Functional multispectral optoacoustic tomography imaging of hepatic steatosis development in mice - Huang, Shan; Blutke, Andreas; Feuchtinger, Annette; Klemm, Uwe; Zachariah Tom, Robby; Hofmann, Susanna M.; Stiel, Andre C.; Ntziachristos, Vasilis (Embo Molecular Medicine, 2021)
The increasing worldwide prevalence of obesity, fatty liver diseases and the emerging understanding of the important roles lipids play in various other diseases is generating significant interest in lipid research. Lipid visualization in particular can play a critical role in understanding functional relations in lipid metabolism. We investigated the potential of multispectral optoacoustic tomography (MSOT) as a novel modality to non-invasively visualize lipids in laboratory mice around the 930nm spectral range. Using an obesity-induced non-alcoholic fatty liver disease (NAFLD) mouse model, we examined whether MSOT could detect and differentiate different grades of hepatic steatosis and monitor the accumulation of lipids in the liver quantitatively over time, without the use of contrast agents, i.e. in label-free mode. Moreover, we demonstrate the efficacy of using the real-time clearance kinetics of indocyanine green (ICG) in the liver, monitored by MSOT, as a biomarker to evaluate the organ’s function and assess the severity of NAFLD. This study establishes MSOT as an efficient imaging tool for lipid visualization in preclinical studies, particularly for the assessment of NAFLD.
CRIS-Team Scopus Importer:2023-03-08
Keywords: biomarker; ICG; lipid metabolism; NAFLD; optoacoustic imaging